How to identify & collect American first editions A guide book - Tannen, Jack (Arco Pub. New York, 1985)
Second edition. The author has supplied a list of over 380 firms and how to tell their first editions. Other interesting material on book collecting included. xii, 142 pages. cloth, dust jacket.. 8vo..
Includes Index and Bibliography
55813
Keywords: First editions -- United States; United States -- Imprints -- Collectors and collecting